2022
DOI: 10.3389/fonc.2022.899262
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Type 2 Diabetes Mellitus on Endometrial Cancer Survival: A Prospective Database Analysis

Abstract: PurposeType 2 diabetes mellitus (T2DM) is an established risk factor for endometrial cancer but its impact on endometrial cancer survival outcomes is unclear. The aim of this study was to investigate whether pre-existing T2DM impacts survival outcomes in endometrial cancer.Patients and MethodsWomen diagnosed with endometrial cancer were recruited to a single centre prospective cohort study. Relevant sociodemographic and clinico-pathological data were recorded at baseline. T2DM status was based on clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
(53 reference statements)
2
5
0
Order By: Relevance
“…Our results align with various other studies [18,22,23,25], which demonstrate a strong association between an increased risk of malignancy and higher BMI, particularly among diabetic women.…”
Section: Discussionsupporting
confidence: 93%
“…Our results align with various other studies [18,22,23,25], which demonstrate a strong association between an increased risk of malignancy and higher BMI, particularly among diabetic women.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of that study were consistent with an earlier review and meta-analysis (2007), showing that diabetes was associated with a 72% increased risk for EC [9,10]. Another larger population-based study emphasized that women with EC and type 2 diabetes mellitus (T2DM) had a twofold higher overall mortality rate, cancer-specific mortality rate, and recurrence rate compared to those without T2DM [11]. In addition, diabetes is also a well-known adverse prognostic factor for short-term outcomes after most surgical procedures, increasing the risk for postoperative complications and reoperations [12,13].…”
Section: Introductionsupporting
confidence: 87%
“…Nevertheless, a meta-analysis of six cohort studies provided inconclusive evidence for establishing a definitive link between diabetes and EC-specific mortality [26]. More recent studies have indicated a two-fold increase in EC-specific mortality among patients with type 2 diabetes mellitus (T2DM) compared to those without [11,27].…”
Section: Results In the Context Of Published Literaturementioning
confidence: 99%
“…Our analysis revealed that women with diabetes had almost double the estimated risk of endometrial cancer compared to women without diabetes. This detected association could be attributed to hyperinsulinemia in type 2 diabetes that contributes to elevated estrogen levels and consequently the development of endometrial cancer [ 5 , 9 ]. Our result is consistent with previous findings which reported an increased risk of endometrial cancer among diabetic women with risk ratios ranging between 1.7 and 2.1 [ 7 15 ].…”
Section: Discussionmentioning
confidence: 99%